Hydrazones of 4-(Trifluoromethyl)benzohydrazide as New Inhibitors of Acetyl- and Butyrylcholinesterase - Krátký, Martin; Svrčková, Katarína; Vu, Quynh Anh; Štěpánková, Šárka; Vinšová, Jarmila (Molecules (Basel, Switzerland), 2021)
Based on the broad spectrum of biological activity of hydrazide-hydrazones, trifluoromethyl compounds, and clinical usage of cholinesterase inhibitors, we investigated hydrazones obtained from 4-(trifluoromethyl)benzohydrazide and various benzaldehydes or aliphatic ketones as potential inhibitors of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). They were evaluated using Ellman's spectrophotometric method. The hydrazide-hydrazones produced a dual inhibition of both cholinesterase enzymes with IC50 values of 46.8-137.7 µM and 19.1-881.1 µM for AChE and BuChE, respectively. The majority of the compounds were stronger inhibitors of AChE; four of them (2-bromobenzaldehyde, 3-(trifluoromethyl)benzaldehyde, cyclohexanone, and camphor-based 2o, 2p, 3c, and 3d, respectively) produced a balanced inhibition of the enzymes and only 2-chloro/trifluoromethyl benzylidene derivatives 2d and 2q were found to be more potent inhibitors of BuChE. 4-(Trifluoromethyl)-N'-[4-(trifluoromethyl)benzylidene]benzohydrazide 2l produced the strongest inhibition of AChE via mixed-type inhibition determined experimentally. Structure-activity relationships were identified. The compounds fit physicochemical space for targeting central nervous systems with no apparent cytotoxicity for eukaryotic cell line together. The study provides new insights into this CF3-hydrazide-hydrazone scaffold.
Keywords: kinetika; hydrazones; Acetylcholinesterase; hydrazides; Butyrylcholinesterase; Blood-Brain Barrier; acetylcholinesterase inhibition; cholinesterasové inhibitory; acetylcholinesterasa; butyrylcholinesterasa; Cholinesterase Inhibitors; Central Nervous System; butyrylcholinesterase inhibition; Hydrazones; hydrazony; centrální nervový systém; Humans; Kinetics; enzyme inhibition; Hydrazines; 4-(trifluoromethyl)benzohydrazide; hematoencefalická bariéra; hydraziny; lidé